Field-effect-induced transport properties of Zn1−xMgxO nanocrystal solid solution. (19th June 2017) - Kim, Youngjun; Yang, Heesun; Park, Byoungnam
Abstract: We report electrical properties of Zn1− x Mg x O nanocrystal solid solution (NCSS) depending on the composition of Mg using a bottom-contact field-effect transistor. In the Zn1− x Mg x O NCSS, as the composition of Mg increases, the field-effect mobility decreases with the threshold voltage shifting to a more positive value. The decrease in the field-effect mobility is attributed to the decrease in the size of the Zn1− x Mg x O NCSS. The increase in the electron trap density in the Zn1− x Mg x O NCSS with the addition of Mg caused a more positive threshold voltage shift. Change in the trap density as a function of Mg composition was demonstrated through comparison of the photoluminescence intensity.